Penguatan Pengelolaan Sampah Yang Bernilai Ekonomis: Desa Sukoanyar, Kecamatan Pakis, Kabupaten Malang, Provinsi Jawa Timur - Chavid Moyo Jaladri; Arief Yuswanto Nugroho; Anudiyan Amir Mas’ud (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2022)
Garbage is a byproduct that has been used by people. The waste at issue is organic waste, with the remainder being inorganic trash. Meanwhile, garbage management is still inefficient, resulting in pollution of the environment. As a result, it is critical to promote environmental stewardship at a young age so that it becomes a habit, and the instructor must also set a positive example for his students. As a result, research on improving the character of environmental care through waste management and the usage of biopori is required to develop an environmental care culture in Sukoanyar Village, Pakis District, Malang Regency. Based on three treatments in strengthening the character of environmental care, including waste sorting and biopore education, making biopore infiltration holes, and managing organic and inorganic waste, the results of this study show an increase in environmental awareness from students in the low category (32.92 percent) to high (80.42 percent).